Conditions for collection of serum samples for the measurement of fibrin(ogen) degradation products by radioimmunoassay of fragment E. Issue 4 (April 1976) - Martin, M J; Gordon, Y B; Ratky, S M; Baker, L R; Chard, T
Abstract : A number of conditions have been assessed for the collection of serum samples for the measurement of fibrin(ogen) degradation products using a radioimmunoassay for degradation fragment E, which permits precise quantitation of differences. Blood should be collected using minimal venous occlusion into glass tubes containing 10 mg/ml of epsilon amino caproic acid and allowed to clot at 4 to 20 degrees C for at least 4 hours before centrifugation. The serum may be stored at 4 or -20 degrees C. Samples from patients receiving anticoagulant therapy should be treated with 10 IU of thrombin per ml.